KEMAMPUAN MENULIS SURAT IZIN SISWA KELAS VII SMP PERTI PADANG TAHUN PELAJARAN 2012/2013 - Muriani, Muriani; Chan, Wirsal; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2013)
Background issue in this study is the lack of student interest in learning to write is to write a letter one of them his own license. Students prefer to ask for help to others and ask for help to write a letter permission. It happened because the students in writing including the fear of being wrong in choosing and determining parts and sub-parts of a letter and use proper diction, effective sentences and the use of spelling will be used. Destination this study was to describe the ability of junior high school students of class VII in terms of Padang Perti three aspects. First, the ability to write part of the license. Second, the ability to use diction. Third, the ability to use words effectively in writing to the schools license. This research is quantitative descriptive method. Descriptive method is used to describe the data obtained. The research sample of junior high school students of class VII Perti Padang taken 25% of the amount of each class. The data of this study is to school letters written permission sample with respect to parts and sub-parts of a letter, EYD, and effective sentence. The results illustrate that the ability to write a letter of permission Perti junior class VII Padang in using sections and sub sections permit the semi-official form letter is in good classification, with an average of 80. Terms of use EYD on classification hampr enough, with an average of 49.33, and in terms of effective use of the phrase is in the classification of almost pretty, with an average of 46.66. Based on three aspects of the above, the ability of students using the effective sentence is at 46.66 which is lowest classification and use parts and sub-parts of the permit form the semi-official letter is at the highest classification that is 80 by using quantitative research.